Terapi Latihan Jalan dan Aktivitas Kognitif Terhadap Masalah Gangguan Interaksi Sosial Pada Lansia di UPT PSTW Jember - Evi Nursyafitri; Fahruddin Kurdi; Septin Wahyu Ersanti (Jurnal Kesehatan Komunitas Indonesia, 2016)
Background: An elderly person is someone aged 60 years and over. The changes experienced by the elderly include declines in biological, psychological, and socioeconomic functions. Psychosocial function is closely related to the quality of life of the elderly. These changes can impact all aspects of life. Walking training combined with cognitive activities can provide benefits and impact the elderly's ability to adapt to changes in psychosocial function. Objective: To determine the impact of walking training and cognitive activities on social interaction disorders at the Jember Community Empowerment and Welfare Unit (UPT) for the Elderly. Methods: This research is a case study of the application of walking training and cognitive activities to address social interaction disorders in an elderly person at Wisma Seruni, Jember's UPT PSTW. The research was conducted over seven days, with three days of intervention. Data collection used observation and assessment methods. Results: After three days of intervention, the client was cooperative and showed improvement in her social interactions. This was evidenced by the assessment results using the DASS and SPMSQ questionnaires, which served as the researcher's reference. Conclusion: Walking exercises will help seniors improve their interactions with other seniors, thereby fostering a sense of community and a sense of appreciation. Furthermore, cognitive activity contributes to adequate thinking and a reduction in feelings of inferiority. Increased interaction with other seniors and cognitive activity also contribute to an improved quality of life for elderly.